المعيقات الدراسية لمهارات القراءة والحساب لدى طلبة الصفوف الثلاثة الأولى في مدارس لواء الأغوار الجنوبية من وجهة نظر المعلمين - الدغيمات، حسين خليل Aldghaimat, Hussein Khalil (جامعة بورسعيد - كلية التربية, 2018)
هدفت الدراسة إلى التعرف على أسباب المعيقات الدراسية لمهارات القراءة والحساب لدى طلبة الصفوف الثلاثة الأولى في مدارس لواء الاغوار الجنوبيه من وجهة نظر المعلمين واكشف عن أثر كل من الجنس، الصف الدراسي، والخبرة التدريسية في المعيقات الدراسية. لتحقيق أهداف الدراسة تم تطوير أداة لقياس المعيقات الدراسية مكونة من (5) مجالات وهي (المعلم، الطالب، المنهاج، بيئة التعلم، الأسرة)، وكان عدد الفقرات الكلي للاستبانة (٥٥) فقرة، وتم التأكد من صدقها وثباتها، وتم توزيعها على عينة مكونة من (٢٠٠) معلما ومعلمه في لواء الاغوار الجنوبية، والذين يدرسون الصفوف الثلاثة الأولى. وللإجابة عن أسئلة الدراسة قام الباحث باستخدام الإحصاء الوصفي (المتوسطات الحسابية، الانحرافات المعيارية)، اختيار ت للعينات المستقلة، وتحليل التباين الأحادي. وقد أظهرت نتائج الدراسة بان المعيقات الدراسية تعود للأسرة بالمرتبة الأولى ثم البيئة الدراسية ثم الطالب ثم المنهاج ثم المعلم، كما بينت الدراسة وعدم وجود فروق إحصائية في التأخر الدراسي يعود للجنس، الصف الدراسي، الخبرة التدريسية في حين اختلفت آراء المعلمين والمعلمات في المعيقات الدراسية، فقد اختلفت الإناث مع الذكور، كما اختلف أصحاب الخبرات التدريسية المتعددة، واختلفت استجابات المعلمين والمعلمات من حيث الصفوف التي يدرسونها وقد خلصت الدراسة إلى عدة توصيات كان من أبرزها دراسة المعيقات الدراسية في محافظات المملكة
Obstacles of reading and numeracy skills among the students of the first three grades in the schools of the Southern Lagoon Brigade from the point of view of the teachers The study aimed at identifying the causes of learning disabilities for reading and numeracy skills among the students of the first three grades in the schools of the Southern Lagoon Brigade from the point of view of the teachers and revealing the impact of gender, class, and teaching experience in the obstacles of study. To achieve the objectives of the study, a tool was developed to measure the obstacles of study consisting of (5) fields (teacher, student, curriculum, learning environment, family). The total number of paragraphs of the questionnaire was (55) (200) teachers and teachers in the Southern Valley, who are studying the first three grades. To answer the study questions, the researcher used descriptive statistics (arithmetical averages, standard deviations), independent sample tests, and single-variance analysis. The results of the study showed that the obstacles to schooling belong to the family in the first place, then the school environment, then the student, then the curriculum, and then the teacher. The study also showed no statistical differences in the school delay due to gender, class, teaching experience, while the views of teachers and teachers differed in the academic obstacles. Women differed with males, and there were differences in the number of teaching experience, and teachers 'and teachers' qualifications differed in terms of the classes they study The study concluded with several recommendations, most notably the study of study obstacles in the Kingdom's governorates
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- المؤسسات التعليمية -- مدارس لواء الأغوار الجنوبية -- الأردن -- المهارات التعليمية -- المعيقات الدراسية -- مستخلصات الأبحاث